Pengaruh Color Gradient, Upper Material, dan Advanced Footwear Technology terhadap Keputusan Pembelian Nike ZoomX - Ramadhan, Nico Putra; Astono, Anjar Dwi (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This study aims to analyze the effect of color gradient, upper material, and advanced footwear technology on purchasing decisions of Nike Zoom X running shoes in Indonesia. A quantitative method was employed with a sample of 153 respondents who had purchased the product, analyzed using multiple linear regression. The results indicate that both partially and simultaneously, all three variables significantly influence purchasing decisions. However, the regression coefficients are negative, suggesting that improvements in these aspects do not necessarily increase purchase decisions, as they are influenced by other factors such as price and perceived value. The Adjusted R² value of 0.645 shows that the model explains 64.5% of the variance in purchasing decisions. This study highlights the importance of balancing product innovation, pricing, and perceived value to enhance product attractiveness in the running shoe market.